Vietnam war almanac - Hillstrom, Kevin (U.X.L. Vietnam War reference library, 2001)
Vietnam War: Almanac traces the progression of this controversial war from its beginnings in 1941 with the creation of the Vietminh guerrilla force under Ho Chi Minh, through its last days in 1975 with the fall of Saigon. Learn more about the people involved with the war in Vietnam War.